Academic Senate Agenda 2014-11-06 - Academic Senate:::::::::
Chair Report. Agenda – Approved. Minutes of 10/23 – Approved. Special Visit: Mayor of Cotati John Dell Osso. Revision to Lecturer's Role in Department Governance policy – First Reading. Graduation Initiative Presentation. President's Report. Vice Chair Report. Vice President of Administration and Finance Report. Associated Students Report. EPC Report. FSAC Report. SAC Report. CFA Report. Good of the Order.